Utilizzo dei dati satellitari per la pianificazione urbanistica: il PUG del comune di Apricena - Barbieri, Vincenzo (GEOmedia, 2010)
Apricena Municipality: using satellite data for urban planning With the entry into force of the Documento Regionale di Assetto Generale (DRAG) Puglia Region has called the 'General Government and land use' for the drafting of the new General Urban Plan. The municipality must pursue the objectives of sustainability environmental maintenance and enhancement of the region through the introduction of procedures for assessing the sustainability of the planning process. In this context, the Strategic Environmental Assessment becomes an integral part of the process of elaboration and approval of the General Urban Plan. DRAG shows the same data by satellite remote sensing between the sources of information that can be used to support the definition of comprehensive cognitive framework of the territory.